Visual Aesthetic Experience and Emotion Regulation among Millennials in City of Imus - Jervin Dinglasan Quicho; Rogemar F. Dela Cruz; Lyka Ueric C. Delos Santos; John Paulo O. Matibag (Future Science / FSH-PH Publications, 2026)
This study examined the relationship between visual aesthetic experience and emotion regulation among 139 millennial residents (aged 29-44) in City of Imus, Cavite. Using a descriptive-correlational design, participants completed the Aesthetic Experience Questionnaire (AEQ) measuring emotional, cultural, perceptual, understanding, flow-proximal conditions, and flow-experience domains, and the Emotion Regulation Questionnaire (ERQ) assessing cognitive reappraisal and expressive suppression. Results revealed that most respondents exhibited low levels of overall visual aesthetic experience (53.2%) and low emotion regulation in both cognitive reappraisal (52.5%) and expressive suppression (54.7%). Spearman Rho correlation analysis demonstrated significant positive relationships between overall aesthetic experience and both cognitive reappraisal (r = 0.461, p < 0.001) and expressive suppression (r = 0.283, p < 0.001), indicating that deeper engagement with visual art corresponds to enhanced emotion regulation capabilities. The cultural domain showed the strongest correlation with cognitive reappraisal (r = 0.487, p < 0.001), while flow-proximal conditions correlated most strongly with expressive suppression (r = 0.326, p < 0.001). Based on these findings, the researchers developed